A photoelectrochemical platform for the capture and release of rare single cells - Stephen G. Parker (Nature Portfolio, 2018)
Many cell capture systems exist but the characterisation and controlled release of single cells is a challenge. Here, the authors report on the development of a duel trigger release system using a combination of photo and electro triggers to allow for light based analysis without unwanted release.